2016
DOI: 10.1158/0008-5472.can-15-3422
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Wnt/β-Catenin in Ewing Sarcoma Cells Antagonizes EWS/ETS Function and Promotes Phenotypic Transition to More Metastatic Cell States

Abstract: Ewing sarcomas are characterized by the presence of EWS/ETS fusion genes in the absence of other recurrent genetic alterations and mechanisms of tumor heterogeneity that contribute to disease progression remain unclear. Mutations in the Wnt/beta-catenin pathway are rare in Ewing sarcoma but the Wnt pathway modulator LGR5 is often highly expressed, suggesting a potential role for the axis in tumor pathogenesis. We evaluated beta-catenin and LGR5 expression in Ewing sarcoma cell lines and tumors and noted marked… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
86
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 76 publications
(103 citation statements)
references
References 52 publications
9
86
0
1
Order By: Relevance
“…To achieve this we interrogated three independent, publicly available databases (13,24,25) and assessed correlations between expression of LEF1 and TNC and COL1A1 in primary patient tumors. We have previously shown that LEF1 is a robust biomarker of Wnt/beta-catenin activation in Ewing sarcoma cells and tumors (14). As shown, expression of TNC was significantly positively correlated with LEF1 in all datasets and COL1A1 correlated with LEF1 in two of the three patient cohorts ( Figure 5C).…”
Section: Wnt Activation In Ewing Sarcoma Cells Promotes Secretion Of supporting
confidence: 60%
See 4 more Smart Citations
“…To achieve this we interrogated three independent, publicly available databases (13,24,25) and assessed correlations between expression of LEF1 and TNC and COL1A1 in primary patient tumors. We have previously shown that LEF1 is a robust biomarker of Wnt/beta-catenin activation in Ewing sarcoma cells and tumors (14). As shown, expression of TNC was significantly positively correlated with LEF1 in all datasets and COL1A1 correlated with LEF1 in two of the three patient cohorts ( Figure 5C).…”
Section: Wnt Activation In Ewing Sarcoma Cells Promotes Secretion Of supporting
confidence: 60%
“…Both of these ECM proteins are well-established mediators of tumor engraftment and metastasis (46,48). We previously showed that stimulation of Ewing sarcoma cells with Wnt3a for 48 hours leads to a two-fold increase in expression of TNC mRNA (14). Analysis of cells following the five-day stimulation protocol used for secretome analysis confirmed robust upregulation of TNC mRNA to greater than five-fold ( Figure 5A).…”
Section: Wnt Activation In Ewing Sarcoma Cells Promotes Secretion Of mentioning
confidence: 63%
See 3 more Smart Citations